Social networks and their added value to companies' promotion. Case study: Tucano Coffee Timisoara - Poterașu, Amina (Technium Social Sciences Journal, 2023)
This study aims to analyse two aspects regarding promotion in social media. The first aspect is the degree of increase in the sales of Tucano Coffee Timisoara products through the promotion of contests and giveaways in social media. The second aspect is represented by the influence of the organization of social media events on the increase in sales of Tucano Coffee Timisoara products. The case study is represented by Tucano Coffee Timisoara due to the fact that more and more people choose this coffee shop in exchange for other dates being the activity of continuous posts in social media. The study used a qualitative and quantitative approach with a methodology of content analysis of the Instagram page of the company Tucano Coffee Timisoara monitored over a period of 3 months, incorporating a literature study and a method of collecting documentary data. The emphasis is placed especially on the importance of product promotion on social networks. The results of this study indicate that the sales of the company's products increase in a rapid way if in the marketing strategy there is an increased attention and care on the social media pages that each company owns. It is also necessary that the activity of the social media pages is in accordance with the followers' preferences.